Safety and Therapeutic Profile of a GnRH-Based Vaccine Candidate Directed to Prostate Cancer. A 10-Year Follow-Up of Patients Vaccinated With Heberprovac - Junco, Jesús A.; Rodríguez, Ranfis; Fuentes, Franklin; Baladrón, Idania; Castro, Maria D.; Calzada, Lesvia; Valenzuela, Carmen; Bover, Eddy; Pimentel, Eulogio; Basulto, Roberto; Arteaga, Niurka; Cid-Arregui, Angel; et al. (Frontiers in Oncology, 2019)
Abstract Heberprovac is a GnRH based vaccine candidate containing 2.4mg of the GnRHm1-TT peptide as the main active principle; 245ug of the very small size proteoliposomes adjuvant (VSSP); and 350uL of Montanide ISA 51 VG oil adjuvant. The aim of this study was to assess in advanced prostate cancer patients the safety and tolerance of the Heberprovac, a GnRH based vaccine candidate and its capacity to induce anti-GnRH antibodies, and in turn, its effects on testosterone production, PSA values and patient survival. Methods Eight patients with indication for hormonal therapy for histologically-proven advanced prostate cancer were recruited. The patients received seven intramuscular immunizations with Heberprovac over four months and a half. Then, their anti-GnRH antibody titers, testosterone, PSA levels and clinical parameters were evaluated. Results The vaccine was well tolerated in the six patients that completed the trial. Significant reductions in serum testosterone and PSA were seen after just four immunizations. Castrate levels of testosterone were observed in all the patients at the end of the immunization schedule, and they remained for more than 20 months. The patients were followed up for 10 years, and only a single death was associated to prostate cancer. Three out of six patients are currently alive and with their hormone-sensitive status. Conclusion This clinical trial showed that it is possible to use a GnRH-based vaccine in prostate cancer patients successfully, and with adequate safety parameters to induce testosterone suppression, PSA normalization, and long-lasting clinical benefits.